"A Good Guy" Again: Biosociality in a Cancer Self-help Organization. Issue 1 (2nd January 2021) - Li, Feifei; Wang, Chadwick
ABSTRACT: The notion of biosociality has been employed in the understanding of forging new forms of social groupings and other forms of social solidarity, with its feasibility and basis challenged in non-Western contexts. According to our study of a Chinese cancer self-help organization, an emergent biosociality occurs through an increasingly common diagnostic biomedical category, cancer. But what truly binds these people tighter is the pre-modern local knowledge of qi, as well as state ideology about living a useful life. A new form of biosocial citizenship, "a good guy ( haoren yige ), " linked to cancer, is thus endowed.